The Physiological Nutrition Basis Of The Cotton Plant With Macro - And Microfertilizers - Rozikova Kamola Elmurodovna, Sanakulov Akmal Lapasovich, (International Journal of Advanced Science and Technology, 2020)
The article describes the effect of macro-and micro-fertilizers on the transpiration rate of thecotton, on the water-retaining ability of cotton leaves, on plastid pigments of leaves, includingchlorophyll pigments "a" and "b", and on carotenoids. It has been studied that one of the importantphysiological characteristics of the plant is the transpiration rate, which changes during the day, asin the phases of its development according to the studied options. The highest transpiration rate wasobserved in the flowering phase of the plant at 2 p.m., as well as in cotton, the planted seeds of whichwere soaked with a solution of microelements of boron and manganese, feeding these solutions fromleaves. If the seeds are sown after treatment with a 0.05% solution of boron and a 0.1% solution ofmanganese, then the ability to accumulate water in the initial phases of cotton is clearly manifested.At the subsequent stages of development, if this indicator is gradually reduced in the same way as inthe control variant without fertilizers, the ability to store water is increased by an average of 3-5%during the development period by reducing the evaporation of water from leaves soaked in microfertilizers solutions. The number of plastid pigments of cotton increases to the flowering phase of theplant and decreases in subsequent periods. The amount of chlorophyll pigment "a" is 3-4 times higherthan the amount of chlorophyll pigment "b", the formation of which is significantly influenced bymacro-and micronutrient fertilizers. If the seeds are sown by treating them with a micro-fertilizersolution, its effect will initially be noticeable at first and decrease without any fluctuations as well asremain at the level of indicators in the background.